An Overview of Consumer Complaining Behavior and the Choice of Complaint Channels in Service Industry - Patwary, Ataul Karim (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2017)
Link to publisher's homepage at http://ijbt.unimap.edu.my